A STUDY ON PACKAGING SELAIS (Cryptoperus bicirchis) CATFISH SAVORY CHIPS - Herry kurniawan; Suparmi '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted at the Laboratory of Technology ofProcessing and Chemical Fisheries, Faculty of Fisheries and Marine SciencesUniversity of Riau, May 2013. The purpose of the research was to study the typeof packed that can protect the quality of the selais catfish savory chips packed inHDPE and LDPE plastic bags during storage. Selais catfish savory chips weremade by mixture of 2 kg of selais catfish meat (67.8 %), rice flour (25 %), garlic(2 %), pepper (1.5 %), coriander (1 %) , salt (2 %), baking soda (0.3 %) and eggs(0.35 %). The savory chips were packed in HDPE and LDPE plastic bags.Changes in quality of selais catfish savory chips were evaluated for sensory andchemical value every 0 , 5 , 10 and 15 days of storage. The results showed that thesensory values (appearance, aroma, texture and taste) of the selais catfish savorychips packed in LDPE plastic bags decreased faster than that packed in HDPEplastic bag, however both of fish chips were still acceptable up to the end of 15days storage. Moisture content and peroxide value of selais catfish savory chipspacked in HDPE and LDPE plastic bags increased during storage but the valueswas lower for the savory chips packed in HDPE than that of LDPE. Fat content ofthe selais catfish savory chips decreased and peroxide value increased duringstorage. The fat composition of the savory chips packed in HDPE decreased fasterthan that of LDPE. More over, peroxide value increased faster for the savory chipspacked in LDPE than that of HDPE. Peroxide values at the end of storage were9.42 and 7.37 for the savory chips packed in LDPE and HDPE respectively.Keywords: Selais catfish, Fish chips, HDPE, LDPE